Provenienz und Kulturgutschutz : Juristische und kunsthistorische Perspektiven - Saß, Ulrike; Saß, Ulrike; Weller, Matthias; Weller, Matthias; Zuschlag, Christoph; Zuschlag, Christoph (Schriftenreihe der Forschungsstelle Provenienzforschung, Kunst- und Kulturgutschutzrecht, 2022)
This volume reveals the potential effects of interdisciplinary cooperation between the areas of provenance research and art and cultural property law. The art historical articles deal with subjects such as cultural assets from colonial contexts, art looted by the Nazis, and the confiscation of cultural assets in the Soviet occupation zone and in the GDR, as well as questions of methodology. The legal articles address the fundamental questions of legal protection of art and cultural assets, for example the implications in terms of civil law of the new Art and Cultural Property Law